2016
DOI: 10.1097/mib.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Providing Our Fellows in Training with Education on Inflammatory Bowel Disease Health Maintenance to Improve the Quality of Care in Our Health Care System

Abstract: Incorporating a standard curriculum on IBD health maintenance provides fellows in training with increased awareness and guidance on managing the unique preventive care needs of patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Quality improvement projects Twelve quality improvement (QI) projects were retrieved from the search, most of which identified process variation and then utilised educational approaches to change clinician behaviour [23,24,[45][46][47][48][49][50][51][52][53]. Table 3 provides a summary of the projects identified.…”
Section: Facilitated Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality improvement projects Twelve quality improvement (QI) projects were retrieved from the search, most of which identified process variation and then utilised educational approaches to change clinician behaviour [23,24,[45][46][47][48][49][50][51][52][53]. Table 3 provides a summary of the projects identified.…”
Section: Facilitated Feedbackmentioning
confidence: 99%
“…They then re-audited after an educational session in which performance against the quality measures was reviewed. Lee at al identified a positive correlation between the intervention and compliance with the quality measures, with compliance increasing by 16% [53]. Two studies progressed this approach by developing algorithms for a range of evidence-based practices as the basis for determining compliance [45,47].…”
Section: Facilitated Feedbackmentioning
confidence: 99%
“…However, the potential risk of comorbidities negatively impacting IBD outcomes has mandated a working knowledge of health maintenance and a holistic approach to healthcare for IBD patients. A recent study showed that incorporating a standard curriculum on IBD health maintenance provided fellows in training with increased awareness and guidance on managing the unique preventive care needs of patients with IBD[172]. Different tools exist to assist practicing gastroenterologists in addressing preventive health issues during clinical encounters with IBD patients, such as, the Crohn’s and Colitis Foundation of America (CCFA) check list for health maintenance or clinical assessment checklist developed by specialized IBD centers[173-175].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported poor compliance with IBD QI measures amongst gastroenterologists [ 12 , 14 , 15 ]. Within gastroenterology, there are additional areas of interest and specialization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that, despite large initiatives for quality improvement in IBD patients, compliance with QI continues to be low [ 12 , 14 - 16 ]. It is, however, encouraging that in our study both groups of physicians exceeded the AGA recommended score of 60.…”
Section: Discussionmentioning
confidence: 99%